Perancangan Simulasi Sistem Pergerakan Menggunakan Metode Register Shiff Pada Pengontrolan Pneumatik Untuk Mesin Pengupas Kelapa Otomatis - Jeffrie J Malakauseya; Josef Matheus (Department of Mechanical Engineering, 2023)
In the field of industry, one of the most important things in a company is the means of production because one of the production processes will not function and it is impossible for the company's goals to be achieved. Production-based industries definitely need tools and machines to support the production process, one of which is a coconut peeler using a pneumatic system. The problem that occurs is how to analyze the movement of air moving on each pneumatic valve to the cylinder that will move the pressure lever. The performance of a pneumatic-based coconut peeler as a medium for testing the simulation was carried out using the register shift method and simulated in the Pneumatic FluidSim Software. The test was carried out directly on the training board in the pneumatic-hydraulic laboratory. The results show that the air flow acts on each pneumatic valve to move the double acting cylinder which functions as a sander block drive. The next step is to determine the type of cylinder with the diameter size used so that it can move the sanding block to move linearly (back and forth). For this reason, it is necessary to calculate the forces (F) acting on the sanding block and how much air pressure (P) is needed Keywords : Software simulasi, FluidSim-Pneumatik, cylinder